Aprendizado espacial-temporal em um ambiente complexo sem restrição alimentar em ratos - Oliveira, Alexsandro Lamarck Duarte (2007)
Timeplace learning is the capacity of organisms to associate both space and time with a biological relevant stimulus such as food. Experiments are usually done with food restricted animals due to the belief that food system activation is necessary for timeplace learning. Another line of thought suggest that, in addition to food system activation, response cost should be increased to effectively allow timeplace discrimination. The purpose of this experiment was to test whether a complex environment, which presumably implied in a heightened response cost, would facilitate timeplace association in satiated rats using a highly palatable food as reward. Nine rats were trained in a timeplace task for 30 nonconsecutive days. A large experimental box (1x1m) divided in four compartments was used. To access each compartment the animal had to overcome a series of obstacles such as ramps, staircases and mazes. Two feeders localized in opposite compartments were rewarded with sunflower seeds in two daily sessions. One feeder offered the reward during the morning sessions while the second feeder in afternoon sessions. After the 15th day of training, the animals began to show a preference for the correct feeder during the correct time of day expressed by increased frequency of visits as well as lower latency to access the feeders. These results suggest that satiated animals are also capable of learning a timespace task as far as the experimental context is complex enough to result in a higher response cost